Green accounting practices for green economic performance on micro, small, and medium enterprises - Chairia, Chairia; Cahyati, Suci; Sabilah, Habel (Indonesia Auditing Research Journal, 2024)
Our environment is facing serious challenges. Many environmental challenges stem from business and entrepreneurial practices that have failed to address environmental sustainability throughout the entire manufacturing chain, from raw material acquisition to customer delivery. Meanwhile, in Indonesia, there is an increase in the number of people beginning businesses. If this tendency continues, it may constitute a significant threat to our environmental sustainability. Micro, Small and Medium Enterprises (MSMEs) have been recognised as one of the key drivers of economic growth in many countries. They are critical to the development of economies as they contribute to job creation, income generation, innovation, and technological advancement. Micro, Small and Medium Enterprises (MSMEs) have great potential to upgrade and contribute more to the local economy. Activist and MSME player, there are a number of challenges that must be overcome, such as the lack of consistency and commitment from MSME players